Antimicrobial activity of marine algal extracts - Ekaterina A Chingizova; Anna V Skriptsova; Michail M Anisimov; Dmitry L Aminin (International Journal of Phytomedicine, 2017)
Total, hydrophilic and lipophilic extracts of 21 marine algae species (2 species of Chlorophyta, 11 of Phaeophyceae and 8 of Rhodophyta) collected along the coast of Russian Far East were screened for antimicrobial activities (against Staphylococcus aureus, Escherichia coli and Candida albicans). Among the macroalgal extracts analyzed, 95% were active against at least one of studied microorganisms, while 80% of extracts were active against two or more test strains. Broad-spectrum activity against three studied microorganisms was observed in the 35% of extracts from tested species of marine seaweeds. The results of our survey did not show clear taxonomic trends in the activities of the total extracts and their hydrophilic fractions against the studied microorganisms. Nevertheless, lipophilic red algal extracts had both the highest values and broadest spectrum of bioactivity among all survey algal extracts. More over, lipophilic extracts from red algal exhibited the highest activity against fungus C. albicans among tested algal extracts.